ADAM28: Another ambivalent protease in cancer. (1st December 2020) - Hubeau, Céline; Rocks, Natacha; Cataldo, Didier
Abstract: Emergence of novel therapeutic options in a perspective of personalized therapy of cancer relies on the discovery of precise molecular mechanisms involved in the switch from a localized tumor to invasive metastasis spread. Pro-tumor functions have been mostly ascribed to proteolytic enzymes from the metalloproteinase family including A Disintegrin And Metalloproteinases (ADAMs). Particularly, when expressed by cancer cells, ADAM28 protease supports cancer cell proliferation, survival and migration as well as metastatic progression. In sharp contrast, ADAM28 derived from the tumor microenvironment has shown to exert strong protective effects against deleterious metastasis dissemination. Indeed, depletion of host-derived ADAM28 (ADAM28 KO mice) accelerates colonization lung tissues, increases tumor foci implantation, and impairs T cell immune response. In this review, we outline specific ADAM28 functions when specifically expressed by carcinoma cells or by tumor microenvironment. Finally, we discuss about future research strategies that could be pursued to highlight new functions of this protease in cancer. Highlights: ADAM28 protease is involved in multiple cancers ADAM28 induces cancer progression via different mechanisms ADAM28 is considered as a potential therapeutic target Depletion of this protease in mice demonstrate protective effects Targeting ADAM28 is questionable since ADAM28 has a potential dual role in cancer